Guilty - Robards, Karen (G.P. Putnam's Sons, 2008)
Kate White, single mother and assistant Philadelphia DA, must fight for her life and the life of her son as the terrible events of her past return with a vengeance and the only hope she seems to have lies with homicide detective Tom Braga--a man she has no reason to trust.